To subtract the expression \(\left(3b-2c\right)-\left(6c+2b\right)-\left(b+c\right)\), we can start by distributing the negative signs across the individual terms.
Here's how to break it down step by step:
-
Rewrite the expression: \[ (3b - 2c) - (6c + 2b) - (b + c) \]
-
Distribute the negative signs: \[ 3b - 2c - 6c - 2b - b - c \]
-
Combine like terms. First, let's combine the \(b\) terms: \[ 3b - 2b - b = (3 - 2 - 1)b = 0b = 0 \]
-
Now, combine the \(c\) terms: \[ -2c - 6c - c = (-2 - 6 - 1)c = -9c \]
-
Putting it all together, we have: \[ 0 - 9c = -9c \]
Thus, the final result of the subtraction is: \[ \boxed{-9c} \]